Survival pattern in male breast cancer: distinct from female breast cancer - Gwark, Sungchan; Kim, Jisun; Chung, Il Yong; Kim, Hee Jeong; Ko, Beom Seok; Lee, Jong Won; Son, Byung Ho; Ahn, Sei Hyun; Lee, Sae Byul (Frontiers in Oncology, 2024)
Male breast cancer (MBC) is a rare condition, and recent research has underscored notable distinctions between MBC and breast cancer in women. This study aimed to assess and contrast the long-term survival outcomes and disease patterns of MBC patients with those of their female counterparts. We analyzed data from 113,845 patients diagnosed with breast cancer who had undergone curative surgery from the Korean Breast Cancer Registry (KBCR) between January 1990 and August 2014 in Seoul, Korea. The five-year overall survival was analyzed according to clinicopathological characteristics. Among 113,845 patients with breast cancer, 473 MBC cases were included. The median duration of follow-up was 72 months. The median age at diagnosis was 60 and 48 years for MBC and female breast cancer, respectively. Most male patients (92.6%) underwent total mastectomy, while 50.4% of female patients underwent breast-conserving surgery. Among MBC, 63.2% received chemotherapy, and 83.9% of hormone receptor-positive male patients received endocrine therapy. In survival analysis, MBC demonstrated distinct 5-year overall survival patterns compared with female breast cancer, according to age at diagnosis. In women with breast cancer, the younger age group (≤40 years) demonstrated worse 5-year overall survival than did the older age group (>40 years) (91.3% vs 92.7%, p <0.05). While in MBC, the younger age group (≤40 years) demonstrated better 5-year overall survival than did the older age group (>40 years) (97.4% vs 86.4%, p <0.05). In conclusion within this extensive cohort, we have revealed unique survival patterns in MBC that diverge from those observed in women with breast cancer. This study enhances our comprehension of MBC prognosis and can potentially shed light on unresolved questions, paving the way for future research in the realm of MBC.